Estimation on conditional restricted mean survival time with counting process. Issue 5 (3rd September 2019) - Qiu, Junshan; Gu, Ennan; Zhou, Dali; Lawrence, John; Bai, Steven; Hung, Hsien Ming J.
ABSTRACT: In traditional survival analyses, hazard ratio (HR) is commonly used to evaluate treatment effects. However, HR may not be easy to interpret. Restricted mean survival time is a viable alternative to HR, particularly when the proportional hazards assumption is not satisfied. We developed a conditional restricted mean survival time (CRMST) estimator for a time interval of interest using counting process. The variance of CRMST was estimated using a perturbation re-sampling method for asymptotic normality. The utility of our CRMST seems promising based on comprehensive simulation studies and a real data case study.